Call to the post: an analysis of Montgomery County equine operators’ motivation for adoption of conservation practices - Ingram, Shelly V. (Kansas State University, 2017)
The equine industry is an established part of Maryland Agriculture; the most recent equine census placed 79,100 equines valued at approximately $714 million in the state, with approximately ten percent of those animals housed in Montgomery County. But, equine operators are a unique demographic in the agricultural realm. They are not managing their lands to produce food or fiber and often are employed in other professions unrelated to agriculture. Unlike other agricultural operators, they are often unaware of conservation terms or practices and programs available to help implement these practices on their land. The basic objective of this study was to explore the level of understanding equine operators in Montgomery County, Maryland have of conservation best management practices (BMPs), associated cost-share programs, industry regulations and the aspects and methods of communication that influence them in gaining awareness of and the adoption of these practices on their properties. The study applied the tenets of the decomposed theory of planned behavior (DTPB), which combines the theory of planned behavior (TPB), diffusion of innovation theory (DOI) and economic constraint theory gathered through semi-structured qualitative interviews with participants, selected using purposive and snowball sampling. Utilizing the grounded theory method to discover emerging patterns in the data resulting from these interviews aided in identifying the most effective means of educating equine operators regarding BMPs and increasing the adoption of these practices on equine properties within the County. Equine operators in the study were found to use a variety of informational sources, had a high level of adaptation of the BMPs they used and overall saw their role as land stewards as an important aspect of their environmental actions.
Keywords: Equine; Best management practices; Decomposed theory of planned behavior; Communication; Conservation; Cost-share